The Impact of Hoaxes to the Business of Information Technology Companies in Indonesia - Nuzirwan, Isabella; Sukandar, Rudi (Journal of Communication and Public Relations, 2021)
The purpose of this research is to investigate whether the impact of hoaxes to an institution is as significant as those to an individual. Besides that, it also to find the impact of the hoax spreading to Indonesian people, especially viewed from the business perspective. The hoax issue investigated in this research is more related to the political ones, but it was viewed from the business perspective, especially business-to-business (B2B). This was a gap in the body of literature that the researchers have found. For this research, researcher utilized mixed methods The first is descriptive qualitative with case study approach where researcher conducted an in-depth interview to several informants, such as business owners and marketing officers from several companies that experienced the effect of hoaxes. The second is quantitative research method with secondary data gathered from the internet. The data analysis showed that hoax issues that hit an institution or company did not have a significant effect compared to those that hit an individual such as a public figure. The researches deliberately chose this hoax topic because it has been popular recently and also the researchers believed that the research using business point of view has not been widely done. Most of the research done today is hoaxes research from political perspective.